Natural and Synthetic Modulators of the TRPM7 Channel - Vladimir Chubanov; Sebastian Schäfer; Silvia Ferioli; Thomas Gudermann (Cells, 2014)
Transient receptor potential cation channel subfamily M member 7 (TRPM7) is a bi-functional protein comprising a TRP ion channel segment linked to an α-type protein kinase domain. Genetic inactivation of TRPM7 revealed its central role in magnesium metabolism, cell motility, proliferation and differentiation. TRPM7 is associated with anoxic neuronal death, cardiac fibrosis and tumor progression highlighting TRPM7 as a new drug target. Recently, several laboratories have independently identified pharmacological compounds inhibiting or activating the TRPM7 channel. The recently found TRPM7 modulators were used as new experimental tools to unravel cellular functions of the TRPM7 channel. Here, we provide a concise overview of this emerging field.